ANALISIS FAKTOR RESIKO LOW BACK PAIN PADA SUPIR TRAVEL ANTAR KOTA ANTAR PROPINSI PADANG-KERINCI - Henky, Jefri; Eka Oktacia, Nelisa (Nusantara Hasana Journal, 2025)
Low Back Pain (LBP) is a result of incorrect ergonomics, the main symptom of LBP is pain in the spinal region of the back. The duration of sitting in a static condition will cause fatigue and the emergence of sore aches. The travel distance from the city of Padang to Kerinci is around 211 km and can be reached in about 7-8 hours with the turns and narrow road conditions. The aims of this study to analyze of the risk factors for LBP of travel drivers in inter-city and inter-provincial in Padang-Kerinci. This study was conducted at the travel counter located in the city of Padang. The design of this study used a cross-sectional with analytical study. The population in the study were all inter-city inter-provincial travel drivers of Padang-Kerinci with 37 samples using total sampling techniques. Data analysis with univariate and bivariate is presented in the form of frequency distribution tables and percentages. Most of the respondents had complaints against LBP with 29 persons (78.4%) with a minimum level of disability is 18 persons (62.1%), respondents aged ≥ 35 years is 30 persons (81.1%), the BMI of respondents was mostly normal is 28 persons (75.7%), all respondents were smokers with the category of heavy smokers is 31 persons (83.8%), most of the respondents had a duration of work > 4 years is 23 persons (62.2%) and most of respondents had a duration of driving > 5 hours is 33 persons (89.2%). Based on the bivariate analysis, there is no relationship between age with LBP p ≥ 0.05, there is a relationship between BMI with LBP p < 0.05, there is no relationship between smoking status with LBP p ≥ 0.05, there is a relationship between length of work with LBP p < 0.05 and there was no relationship between duration of driving with LBP p ≥ 0.05. From this study, it was concluded that there was no relationship between age with LBP, there was a relationship between BMI with LBP, there was no relationship between smoking status with LBP, there was a relationship between length of work with LBP and there was no relationship between driving duration with LBP.